Review of the theoretical underpinnings in the creative tourism research field - Rui Miguel Ferreira Carvalho; Carlos Manuel Martins da Costa; Ana Maria Alves Pedro Ferreira (Tourism & Management Studies)
Despite the rising number of creative tourism publications, creative tourism is still emerging as a recent research area. Its study ranges from urban cities to rural areas implicating different uses for creativity, culture, events, creative networks and the co-creation of experiences. This paper had the goal to focus on the main theoretical subjects of creative tourism as a research area. As a result, the authors pinpoint vital issues present in creative tourism literature even though its definition is still evolving. After a thorough literature review, the authors conceptualised three main theoretical contributions present in creative tourism literature: 1) creativity and its relation to tourism, (2) specialised consumption as a characteristic of the postmodern tourist and 3) the experience economy paradigm and co-creation. This study identifies the main theoretical underpinnings of creative tourism, which made this special interest tourism gain so much importance in recent years